Matrično konveksne množice - Klep, Igor (Obzornik za matematiko in fiziko, 2016)
In this article we explore a natural extension of the notion of convexity to matrix spaces, the so-called matrix convex sets. We shall give an appropriate analog of the Hahn-Banach theorem and present some of its applications.
Keywords: konveksnost